2020
DOI: 10.7554/elife.57306
|View full text |Cite
|
Sign up to set email alerts
|

Interaction mapping of endoplasmic reticulum ubiquitin ligases identifies modulators of innate immune signalling

Abstract: Ubiquitin ligases (E3s) embedded in the endoplasmic reticulum (ER) membrane regulate essential cellular activities including protein quality control, calcium flux, and sterol homeostasis. At least 25 different, transmembrane domain (TMD)-containing E3s are predicted to be ER-localised, but for most their organisation and cellular roles remain poorly defined. Using a comparative proteomic workflow, we mapped over 450 protein-protein interactions for 21 stably expressed, full-length E3s. Bioinformatic an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 136 publications
(193 reference statements)
2
59
0
Order By: Relevance
“…We did not yet identify the E3 ubiquitin ligase which is required for UBE2N-mediated ubiquitination of EVI/WLS, but our data and recently published high-throughput studies indicate that it is presumably not an ER-membrane associated protein, but rather cytosolic (Fenech et al, 2020;Leto et al, 2019;Glaeser et al, 2018). It should also be considered that earlier in vitro and structural studies showed that UBE2N~ubiquitin together with UBE2V2 can adopt its active conformation even in the absence of an E3 ligase, suggesting E3 independent ubiquitin chain elongation (McKenna et al, 2001;Pruneda et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We did not yet identify the E3 ubiquitin ligase which is required for UBE2N-mediated ubiquitination of EVI/WLS, but our data and recently published high-throughput studies indicate that it is presumably not an ER-membrane associated protein, but rather cytosolic (Fenech et al, 2020;Leto et al, 2019;Glaeser et al, 2018). It should also be considered that earlier in vitro and structural studies showed that UBE2N~ubiquitin together with UBE2V2 can adopt its active conformation even in the absence of an E3 ligase, suggesting E3 independent ubiquitin chain elongation (McKenna et al, 2001;Pruneda et al, 2011).…”
Section: Discussionmentioning
confidence: 57%
“…It is known that EVI/WLS is ubiquitinated by UBE2J2 and CGRRF1 (Fenech et al, 2020;Glaeser et al, 2018) and that the UBE2J2 ortholog in yeast (Ubc6) is indispensable for priming a broad range of substrates with monoubiquitin or K11-linked ubiquitin dimers (Weber et al, 2016;Xu et al, 2009). However, so far the kind of ubiquitin linkage types present on EVI/WLS and the sites of its modification have not been identified, since the TUBEs used to detect ubiquitination in Figure 5D were non-selective and unable to distinguish between different ubiquitin linkage types.…”
Section: Erlin2 Connects Evi/wls To the Ubiquitination Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that ENDOD1 is a cytoplasmic nuclease ( Figure 1a) involved in innate immunity as part of the RNF26-mediated cGAS-STING pathway 6 . The unexpected identification of ENDOD1 as a PARPi-responsive protein lead us to examine its potential role in DNA repair.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cholesterol-associated formation of ER-endosomes MCSs, ubiquitin-mediated events, such as those regulated by the ER-embedded ubiquitin ligase ring finger-containing protein 26 (RNF26), ubiquitin-conjugating enzymes E2 J1 (UBE2J1) and sequestosome 1 (SQSTM1; also known as p62) complex (Cremer et al, 2020 preprint;Jongsma et al, 2016) can also support reversible connections between these organelles. Interestingly, recent proteomic findings suggest that RNF26 resides in a complex with various members of the ER Ca 2+ efflux machinery, including IP3R1 and SigmaR1 (Fenech et al, 2020). The observed dynamics of lysosomes at IP3R clusters parallel those of endolysosomes that reversibly associate with the ER via In the course of their maturation, endosomes travel into the cell interior (towards the minus-end of microtubules); this requires active transport that is mediated by the cholesterol-sensitive RILP-dynein complex, or the Ca 2+ -responsive ALG2-dynein complex.…”
Section: Tuning Cellular Metabolism At Er-mitochondria Mcssmentioning
confidence: 99%